Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcvm.2022.807339
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Neutrophil to High-Density Lipoprotein Cholesterol Ratio for All-Cause and Cardiovascular Mortality in the General Population

Abstract: BackgroundNeutrophil counts to high-density lipoprotein cholesterol ratio (NHR), a composite marker of inflammation and lipid metabolism, has been considered as a predictor of clinical outcomes in patients with acute ischemic stroke and acute myocardial infarction. However, the predictive value of NHR for all-cause and cardiovascular mortality in the general population remains unclear.MethodsOur study population comprised 34,335 adults in the United States obtained from the National Health and Nutrition Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
(47 reference statements)
1
22
0
Order By: Relevance
“… 2 A study based on an inflammatory model in vitro and in vivo displayed that neutrophils play a pathogenic role in the immune-inflammatory response in atherosclerosis pathogenesis. 33 Neutrophils are one of the first cells to react in the blood after an ischemic stroke. They can lead to the breakdown of the BBB and brain damage by mediating various inflammatory factors such as ROS, proteases, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“… 2 A study based on an inflammatory model in vitro and in vivo displayed that neutrophils play a pathogenic role in the immune-inflammatory response in atherosclerosis pathogenesis. 33 Neutrophils are one of the first cells to react in the blood after an ischemic stroke. They can lead to the breakdown of the BBB and brain damage by mediating various inflammatory factors such as ROS, proteases, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data, including age, sex and race, were collected by questionnaires. People who had smoked over 100 cigarettes during their lifetime were regarded as smokers ( 21 ). A history of present illness (e.g., heart failure, coronary artery disease and stroke) and medication treatment were obtained from self-reported personal interview data.…”
Section: Methodsmentioning
confidence: 99%
“…11 14-18 In addition, a general population from the USA showed that NHR is a predictor of all-cause and cardiovascular mortality. 19 LHR was proposed by Chen et al 12 as a novel inflammatory indicator. Consistent with the results from Chen et al, 12 other studies have confirmed the role of LHR in predicting the presence and severity of metabolic syndrome.…”
Section: Original Researchmentioning
confidence: 99%
“…Moreover, it has been found that MHR and NHR are risk factors for severe stenosis and poor prognosis in patients with CAD 11 14-18. In addition, a general population from the USA showed that NHR is a predictor of all-cause and cardiovascular mortality 19. LHR was proposed by Chen et al 12 as a novel inflammatory indicator.…”
Section: Introductionmentioning
confidence: 99%